Targeting chemokine signaling networks for therapeutics in skeletal disorders - Gao, Wenjie; Gao, Zhiheng; Chen, Yu; Wang, Yu; Li, Yonggang; Qian, Yuchen; Lu, Haowen; Ling, Xuwei; Xiao, Heting; Yang, Peng; Qiao, Yusen (Frontiers in Endocrinology, 2025)
Chemokine signaling networks have emerged as pivotal regulators of skeletal homeostasis, integrating inflammation, angiogenesis, and immune activation with the processes of bone remodeling and regeneration. Recent evidence demonstrates that dysregulated chemokine–receptor interactions, including CCL2/CCR2, CCL5/CCR5, and CX3CL1/CX3CR1, disrupt the equilibrium between osteogenesis and osteoclastogenesis, thereby contributing to the pathogenesis of osteoporosis, osteoarthritis, multiple myeloma, and bone metastasis. This review synthesizes current insights into how chemokine-mediated signaling cascades intersect with canonical pathways such as JAK/STAT3, NF-κB, PI3K/Akt, and Wnt/β-catenin to coordinate cellular communication within the bone microenvironment. Furthermore, it highlights recent progress in therapeutic strategies targeting chemokine axes to mitigate inflammatory bone loss and promote tissue regeneration, while addressing translational barriers including receptor redundancy, context-dependent specificity, and limited in vivo validation. By positioning chemokines as dynamic mediators at the interface of the immune and skeletal systems, this review establishes a conceptual foundation for the development of precision therapeutics aimed at restoring bone homeostasis and treating skeletal disorders.